Exercise induces biventricular mechanical dyssynchrony in children with repaired tetralogy of Fallot. Issue 24 (18th November 2010) - Roche, S Lucy; Grosse-Wortmann, Lars; Redington, Andrew N; Slorach, Cameron; Smith, Gareth; Kantor, Paul F; Friedberg, Mark K
Abstract : Objective: The mechanisms underlying adverse electro-mechanical interaction after tetralogy of Fallot (TOF) repair remain unclear. This study investigated biventricular dyssynchrony in children with TOF and its relationship to exercise, QRS duration (QRSd) and ventricular mechanics. Methods: 29 asymptomatic children (5–18 years) with repaired TOF were prospectively evaluated by MRI, cardiopulmonary exercise testing and echocardiography at rest and during bicycle exertion. Their dyssynchrony results were compared with those of 44 resting and 27 exercising, age- and sex-matched controls. An intraventricular dyssynchrony index was calculated from the SD of regional time intervals in 12 left ventricular (LV) 'Ts LV-12SD' and eight right ventricular (RV) 'Ts RV-8SD' segments. Ventricular size, volumes, ejection fractions, pulmonary regurgitant volumes and peak oxygen consumption and N-terminal BNP levels were quantified in the patients. Results: Despite moderate RV dilatation (median indexed RV end-diastolic volume 145.2 ml/m 2 ) and right bundle branch block (median QRSd 130 ms) compared with controls, children with TOF demonstrated neither RV nor LV dyssynchrony at rest (Ts RV-8SD, 37.9±10.2 vs 44.3±10.3, 95% CI −11.8 to −0.99, p=0.02; Ts LV-12SD, 38.6±16.8 vs 34.0±10.8, 95% CI −1.8 to 11.0, p=0.16). Exercise stress induced biventricular dyssynchrony in patients with TOF but not in controls (Ts RV-8SD, 59.9±34.4 vs 28.2±10.4, p<0.0001, 95% CI 17.2 to 46.3; Ts LV-12SD, 48.0±18.6 vs 31.9±10.7, 95% CI 7.9 to 24.4, p=0.002). This was unrelated to QRSd, ventricular volumes and function, or peak oxygen consumption. Conclusion: Exercise induces biventricular mechanical dyssynchrony in children with TOF.